Sperm DNA Fragmentation and Chromatin Maturation of Prepared Sperm with ALA Supplementation: The Effect of Embryo Development Quality - silvia werdhy lestari; aucky hinting; Petrus Supardi; anom Bowolaksono; asmarinah asmarinah (Journal of Global Pharma Technology, 2019)
Abstract: This study was aimed to determine the differences in embryo quality between spermatozoa with good or poor of DNA fragmentation index and chromatin maturation, through spermatozoa preparation with the addition of ALA. This experimental study compared the quality of embryos that fertilized by spermatozoa with DNA fragmentation and chromatin maturation, with and without ALA supplementation. In this study semen samples from 20 patients were collected, which were then prepared and examined for DNA fragmentation index (DF) and chromatin maturation (CM). Then the sample was divided into 4 groups, namely the good DF - good CM, good DF - poor CM, poor DF - good CM and poor CM - poor CM, further divided again with and without treatment (ALA supplementation). After injection of spermatozoa into the oocyte, the development of embryo was observed in each group. In the group without treatment, significant differences in embryo quality were obtained between groups of good DF - good CM with poor DF - good CM, good DF - good CM with poor DF - poor CM, good DF - poor CM with poor DF - good CM and good DF - poor CM with poor DF - poor CM (p <0.05). In the treatment group, there were not significant difference in the quality of the embryo between treatment groups, namely with or without ALA, in the group with good or poor DF, and with good or poor CM (p> 0.05). Embryo fertilized by spermatozoa with good or poor DF and with good or poor CM, with the supplementation of ALA, the quality was not significantly better than without the supplementation of ALA.    Keywords: spermatozoa DNA fragmentation, spermatozoa chromatin maturation, ALA, in vitro fertilization, embryo quality